APPLICATION SYSTEM EQUIPMENT SALES OFFICE IN CV WRITING. REDIKO PERMATA USING MICROSOFT VISUAL FOXPRO 9.0 - Ruri Lucyta Sari; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2010)
Cv. Rediko Permata is one company engaged in the sale of office stationery.Constraints faced by Cv. Rediko Permata is the confusion of data and datakerangkapan caused by data that are not processed properly. Also difficult to find theremaining inventory is still there and the goods have been sold. This is due to still usethe manual system and the data has not been computerized. Alternative solutions thatcan be done to improve corporate performance Cv. Rediko Permata is to build anapplication of a computerized sales system in accordance with the times and changesthat continue to rise. The system enables data entry process, the change data andmaking reports will be very easy to do so that data processing can be resolvedquickly, precisely and accurately. For that made an application using MicrosoftVisual FoxPro 9.0. Microsoft Visual FoxPro 9.0 is a database application designprograms that are widely used today, other than the display is easy to use in MicrosoftVisual FoxPro 9.0 is also more interesting. Applications created with MicrosoftVisual FoxPro 9.0 to assist Cv Permata Rediko It contains a database, table, forms,reports and menus that can support Cv. Rediko Permata in managing sales data sothat data can be minimized confusion.